Magic eye III visions : a new dimension in art-- 3D illusions (Kansas City, MO : Andrews and McMeel, 1994)
Computer-generated 3D picture puzzles challenge viewers to find the images within images.
6.5
5-8
Keywords: Visual perception; Optical illusions; Visual perception; Optical illusions; Computer art